Unique Location of the Chest Wall Hydatid Cyst: A Case Report (Iraqi Journal of Medical Sciences, 2024)
The chest wall hydatidosis is a rare location of primary hydatid cyst. This is a 29-old female, multipara presented with a right anterior chest wall painless swelling below the clavicle deep to the pectoralis major muscle). Investigations confirm that this is a chest wall cystic lesion most likely hydatid cyst and it is the only one, no other organ involved. Patient prepared for surgery, the cyst completely removed successfully under general anesthesia and the histological examination confirm a hydatid cyst of the chest wall).Keywords: Chest wall cyst, hydatid cyst.Citation: Mohialdeen SA. Unique location of the chest wall hydatid cyst: A case report. Iraqi JMS. 2024; 22(2): 422-426. doi: 10.22578/IJMS.22.2.27
Keywords: Chest wall cyst; hydatid cyst